Comparatıve Analysıs Of Enzymatıc Changes In Dıfferent Lınes Of Brachypodıum Dıstachyon Under Rust Infectıon - N. Omirbekova, A. Zhussupova, Zh. Zhunusbayeva, B. Yertaeva, G. Demzhanova, S. Kenzhebaeva (International Journal of Advanced Science and Technology, 2020)
From the ancient times, humanity has been growing cereals, of which wheat is regarded at present as the most important staple food. Under current conditions of growing shortage of wheat, humanity might once again face an acute problem of the food crisis. Rust, the most common infector of wheat, is widely dispersed on the territory of CIS with 20-25% of infected rust annually. Creation of pathogen-resistant varieties of cultivated plants by methods of traditional breeding is long-term, and the evolution of pathogens is ahead of the possibilities of practical breeding, resulting in creation of varieties resistant to pathogens being late with their introduction into the production cycle. Our scientific group is the first in Kazakhstan, engaged in detailed studies on the use of Brachypodium distachyon as a model object for studying changes caused by the brown rust pathogen. Some results of this study are presented in the current paper.